2019
DOI: 10.1038/s41598-019-42770-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of adipose tissue GLP-1R expression in metabolic improvement after bariatric surgery in patients with type 2 diabetes

Abstract: We aimed to explore the relationship between GLP-1 receptor ( GLP-1R ) expression in adipose tissue (AT) and incretin secretion, glucose homeostasis and weight loss, in patients with morbid obesity and type 2 diabetes undergoing bariatric surgery. RNA was extracted from subcutaneous (SAT) and visceral (VAT) AT biopsies from 40 patients randomized to metabolic gastric bypass, sleeve gastrectomy or greater curvature plication. Biochemical parameters, fasting plasma insulin, glucagon and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 38 publications
(54 reference statements)
0
18
0
Order By: Relevance
“…Liraglutide has also been shown to reduce total adiposity, and specifically visceral fat mass (582,583). While initially described as being devoid of GLP-1 receptors (584), it has now been confirmed that adipocytes express the GLP-1 receptor (585,586). Adipose tissue may therefore be an additional target for GLP-1 receptor agonists to promote adipose remodeling by unknown mechanisms.…”
Section: Glp-1 Receptor Agonistsmentioning
confidence: 99%
“…Liraglutide has also been shown to reduce total adiposity, and specifically visceral fat mass (582,583). While initially described as being devoid of GLP-1 receptors (584), it has now been confirmed that adipocytes express the GLP-1 receptor (585,586). Adipose tissue may therefore be an additional target for GLP-1 receptor agonists to promote adipose remodeling by unknown mechanisms.…”
Section: Glp-1 Receptor Agonistsmentioning
confidence: 99%
“…Accordingly, the factors affecting metabolic surgery mediated antihypertension need to be identified. Some studies suggest that gut hormones may be a potential target for the treatment of hypertension because metabolic surgery increases GLP‐1 secretion 19 . Our previous research showed that metabolic surgery significantly antagonised the activation of the sympathetic nerve system in both human and experimental hypertensive models 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Ejarque, et al showed that 1 year after surgery, the increase in the area under curve (AUC) for GLP-1 was significantly higher in the RYGB group than in SG. Less clear is the extent to which GLP-1 changes are responsible for T2DM remission [23].…”
Section: Discussionmentioning
confidence: 99%